PENGARUH VARIABEL EKONOMI MAKRO DAN INDEKS HARGA SAHAM DUNIA TERHADAP JAKARTA ISLAMIC INDEX - Basuki, Agus Tri; Yusuf, A. Indriyani (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2018)
Effect of Macroeconomic Variables and World Stock Price Index on the Jakarta Islamic Index. The purpose of this research is to find out the influence of Dow Jones Industrial Average (DJIA) index, Nikkei 225 (N225), Shanghai Stock Exchange Composite Index (SSECI), exchange rate (Rupiah to Dollar) and Gross Domestic Product (GDP) to Jakarta Islamic Index (JII). This research uses Vector Error Correction Model (VECM) in analyzing data or variables. VECM is a derivative method of VAR. The assumptions that must be met in this VECM model are the same as those in the VAR model. The findings of this study are that DJIA has a negative and significant effect on JII as a shock absorber in the short and long term. N225 has a positive and significant effect on JII in the short and long term. SSECI in the short term does not affect the movement of JII. While in long term SSECI have negative and significant influence to JII. KURS in the short term have a positive and significant effect on JII. While in the long term KURS does not affect JII. GDP in the short term has a positive and significant impact on JII. While in the long run the GDP does not affect the movement of JII